2006
DOI: 10.1002/glia.20441
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin regulates oligodendroglial process dynamics and survival

Abstract: Simvastatin, a lipophilic statin that crosses the blood-brain barrier, is being evaluated as a potential therapy for multiple sclerosis (MS) due to its anti-inflammatory properties. We assessed the effects of simvastatin on cultures of rat newborn and human fetal oligodendrocyte progenitor cells (OPCs) and human adult mature oligodendrocytes (OLGs) with respect to cellular events pertaining to myelin maintenance and repair. Short-term simvastatin treatment of OPCs (1 day) induced robust process extension, enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
97
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(111 citation statements)
references
References 68 publications
12
97
2
Order By: Relevance
“…9D), which is consistent with netrin 1 not increasing the activation of Cdc42 in oligodendrocytes. Inhibiting RhoA, or its downstream effector Rho kinase (Rock1/2), in oligodendrocytes increases process extension (Liang et al, 2004;Miron et al, 2007;Wolf et al, 2001). Interestingly, activation of Fyn in oligodendrocytes leads to inactivation of RhoA (Wolf et al, 2001), and we therefore investigated the possibility that netrin 1 might regulate RhoA activity in oligodendrocytes.…”
Section: Netrin 1 Inhibits Rhoa But Does Not Affect Cdc42 or Rac1 In mentioning
confidence: 99%
“…9D), which is consistent with netrin 1 not increasing the activation of Cdc42 in oligodendrocytes. Inhibiting RhoA, or its downstream effector Rho kinase (Rock1/2), in oligodendrocytes increases process extension (Liang et al, 2004;Miron et al, 2007;Wolf et al, 2001). Interestingly, activation of Fyn in oligodendrocytes leads to inactivation of RhoA (Wolf et al, 2001), and we therefore investigated the possibility that netrin 1 might regulate RhoA activity in oligodendrocytes.…”
Section: Netrin 1 Inhibits Rhoa But Does Not Affect Cdc42 or Rac1 In mentioning
confidence: 99%
“…More recently, pharmacologic induction of OPC differentiation by inhibition of RhoA-Rho-kinase II (ROCK-II), and/or protein kinase C signaling [108], or by anti-Leucine-rich repeats and Ig domain-containing, neurite outgrowth inhibitor (Nogo) receptor-interacting protein-1 (LINGO1) antibodies [109,110] accelerated remyelination. Statins and inhibitors of receptor tyrosine phosphatases are other pharmacologic agents that induce rodent [111] and human [112] oligodendrocyte differentiation. However, when tested in the cuprizone model of demyelination in vivo, statin therapy inhibited remyelination [113].…”
Section: Myelin Regeneration Fails In Msmentioning
confidence: 99%
“…Subsequent studies with purified oligodendrocytes also reported that short-term treatment with simvastatin also induced differentiation to the mature phenotype via inactivation of RhoA. However, longer term treatment was associated with process retraction and cell death [69]. The observed increase in oligodendrocyte precursors, their differentiation and expression of myelin-related genes in mixed glial cultures and in EAE [10], as compared with the effects observed with purified oligodendrocytes [69], all indicate that trophic molecules secreted by astrocytes and microglia may potentiate the effects of statins.…”
Section: Statins Support Remyelinationmentioning
confidence: 94%
“…However, longer term treatment was associated with process retraction and cell death [69]. The observed increase in oligodendrocyte precursors, their differentiation and expression of myelin-related genes in mixed glial cultures and in EAE [10], as compared with the effects observed with purified oligodendrocytes [69], all indicate that trophic molecules secreted by astrocytes and microglia may potentiate the effects of statins. The observed increased expression of transcription factors and trophic factors responsible for proliferation of oligodendrocyte progenitors, and transcription factors for their differentiation into myelin producing oligodendrocytes in lovastatin-treated animals during disease remission, may contribute to the observed remyelination in animals with EAE treated with lovastatin [10].…”
Section: Statins Support Remyelinationmentioning
confidence: 96%
See 1 more Smart Citation